1979
DOI: 10.3109/03009737909179142
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Short-term High-dose Treatment with Methenamine Hippurate of Urinary Infection in Geriatric Patients with Indwelling Catheters

Abstract: The u r i n e sediment of 12 g e r i a t r i c p a t i e n t s w i t h i n d w e l l i n g c a t h e t e r s was quant i f i e d by t h e glutaraldehyde-cytocentrifuge method p r i o r t o , d u r i n g and a f t e r a c l i n i c a l t r i a l of methenamine h i p p u r a t e (MH), 2 g x 3 d a i l y g i v e n f o r 34 days as t h e s o l e t h e r a p e u t i c agent f o r u r i n a r y t r a c t i n f e c t i o n . c o n c e n t r a t i o n i n t h e u r i n e of t h e s e p a t i e n t s w a s 100 c e l l s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…77 Most studies of this agent have been small, nonrandomized trials in geriatric institutions. Using a before-and-after intervention design, oral methenamine hippurate therapy (2-6 g/d) was found to reduce the incidence of bacteriuria, 77,78 symptomatic UTI, 79 and pyuria. 80 One large, nonrandomized, comparative trial 81 found that patients receiving methenamine hippurate had significantly fewer courses of antibiotic drug therapy for symptomatic UTI and less frequent mechanical catheter complications.…”
Section: Methenamine Hippuratementioning
confidence: 99%
“…77 Most studies of this agent have been small, nonrandomized trials in geriatric institutions. Using a before-and-after intervention design, oral methenamine hippurate therapy (2-6 g/d) was found to reduce the incidence of bacteriuria, 77,78 symptomatic UTI, 79 and pyuria. 80 One large, nonrandomized, comparative trial 81 found that patients receiving methenamine hippurate had significantly fewer courses of antibiotic drug therapy for symptomatic UTI and less frequent mechanical catheter complications.…”
Section: Methenamine Hippuratementioning
confidence: 99%